2016
DOI: 10.4238/gmr.15027578
|View full text |Cite
|
Sign up to set email alerts
|

Structure of mitochondrial DNA control region and genetic diversity of Moschus berezovskii populations in Shaanxi Province

Abstract: ABSTRACT. In China, Moschus berezovskii (forest musk deer), a firstclass national protected animal, was earlier widely distributed. However, wild populations of the forest musk deer have declined because of human activity and habitat loss. In order to gather useful information for its conservation and management, we investigated the genetic diversity and population structure of this species by analyzing a 632-bp fragment of mitochondrial DNA (mtDNA) control region in three wild populations in Shaanxi Province,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 13 publications
(11 reference statements)
1
9
1
Order By: Relevance
“…In recent years, many molecular markers have been used to investigate the phylogeny and biogeography of insect populations (Chatterjee and Tanushree, 2004;Behura, 2006). Due to their strictly maternal inheritance, high evolutionary rates, and lack of recombination, mitochondrial DNA genes have been a popular choice as markers for studying population genetic structures (Avise, 1991;Sunnucks, 2000;Behura, 2006;Feng et al, 2016). Both of the mitochondrial DNA genes cytochrome oxidase subunit I (COI) and cytochrome b (Cytb) have a moderate evolutionary rate, and a clear evolutionary pattern that is suitable for studies of phylogenetic evolution at the intra-and interspecific levels (Hebert et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many molecular markers have been used to investigate the phylogeny and biogeography of insect populations (Chatterjee and Tanushree, 2004;Behura, 2006). Due to their strictly maternal inheritance, high evolutionary rates, and lack of recombination, mitochondrial DNA genes have been a popular choice as markers for studying population genetic structures (Avise, 1991;Sunnucks, 2000;Behura, 2006;Feng et al, 2016). Both of the mitochondrial DNA genes cytochrome oxidase subunit I (COI) and cytochrome b (Cytb) have a moderate evolutionary rate, and a clear evolutionary pattern that is suitable for studies of phylogenetic evolution at the intra-and interspecific levels (Hebert et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The AFLP was first applied to measure genetic diversity of two populations of captive musk deer populations in Baisha of Sichuan and at a reserve in Jinfeng Mountains, and both populations had high genetic diversity [21,27], but the population in Jinfeng Mountain was higher than that in Baisha [21]. Peng et al detected 27 haplotypes by analyzing the mitochondrial DNA (mtDNA) D-loop sequence of three captive musk deer herds in Sichuan Province [23], and Feng et al also studied the mtDNA D-loop sequence of one captive population and three wild groups in Shaanxi Province, China [24]. They found that the mtDNA D-loop sequence of musk deer in Shaanxi Province showed considerable variation [23,24].…”
Section: Genetic Characteristics Of Captive Musk Deer Populationmentioning
confidence: 99%
“…Peng et al detected 27 haplotypes by analyzing the mitochondrial DNA (mtDNA) D-loop sequence of three captive musk deer herds in Sichuan Province [23], and Feng et al also studied the mtDNA D-loop sequence of one captive population and three wild groups in Shaanxi Province, China [24]. They found that the mtDNA D-loop sequence of musk deer in Shaanxi Province showed considerable variation [23,24]. The genetic differentiation of both wild and captive groups was small, but there was a high degree of exchange of genetic material [24].…”
Section: Genetic Characteristics Of Captive Musk Deer Populationmentioning
confidence: 99%
See 2 more Smart Citations